De novo Taproot Transcriptome Sequencing and Analysis of Major Genes Involved in Sucrose Metabolism in Radish (Raphanus sativus L.) - Yu, Rugang; Xu, Liang; Zhang, Wei; Wang, Yan; Luo, Xiaobo; Wang, Ronghua; Zhu, Xianwen; Xie, Yang; Karanja, Benard; Liu, Liwang (Frontiers in Plant Science, 2016)
Radish (Raphanus sativus L.) is an important annual or biennial root vegetable crop. The fleshy taproot comprises the main edible portion of the plant with high nutrition and medical value. Molecular biology study of radish begun rather later, and lacks sufficient transcriptomic and genomic data in pubic databases for understanding of the molecular mechanism during the radish taproot formation. To develop a comprehensive overview of the ‘NAU-YH’ root transcriptome, a cDNA library, prepared from three equally mixed RNA of taproots at different developmental stages including pre-cortex splitting stage, cortex splitting stage and expanding stages was sequenced using high-throughput Illumina RNA sequencing. From approximately 51 million clean reads, a total of 70,168 unigene with a total length of 50.28 Mb, an average length of 717 bp and a N50 of 994 bp were obtained. In total, 63,991 (about 91.20% of the assembled unigenes) unigenes were successfully annotated in five public databases including NR, GO, COG, KEGG and Nt. GO term analysis revealed that the majority of these unigenes were predominately involved in basic physiological and metabolic processes, catalytic, binding and cellular process．In addition, a total of 103 unigenes encoding eight enzymes in the sucrose metabolism related pathways were also identified by KEGG pathways analysis. Sucrose synthase (29 unigenes), invertase (17 unigenes), sucrose-phosphate synthase (16 unigenes), fructokinase (16 unigenes) and hexokinase (11 unigenes) ranked top five enzymes in these eight key enzymes. From which, two genes (RsSuSy1, RsSPS1) were validated by T-A cloning and sequenced in radish, while six unigenes were validated by RT-qPCR analysis. These results would be served as an important public reference platform to identify the related key genes during taproot thickening and facilitate the revealing of molecular mechanisms underlying taproot thickening in radish.